Isolation of Anthocyanidin from Wora-Wari Flowers (Hibiscus rosa sinensis L.) and Its Application As Indicators of Acid-base - Siti Nuryanti; Indarini Dwi Puspitasari; Ratman Ratman (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
Wora-wari plants are easily cultivated and founded in Indonesia, also their bloomy is not seasonal. Isolation of anthocyanidin from Wora-wari was done by maceration using n-hexane, ethyl acetate and methanol-HCl 1.0% and isolation of anthocyanidin was performed by column chromatography. Identification for structure of anthocyanidin was done by UV-Vis spectrophotometer, FT-IR, 1H- and 13C-NMR along with color reagent. In the Wora-wari flowers, it has been identified the existence of anthocyanidin pelargonidin. The color change of anthocyanidin pelargonidin results in acid solution was red and base solution was green.